MANGROVE COVER-BASED VEGETATION INDICES MAPPING USING PLANETSCOPE DATA IN TIEN YEN DISTRICT QUANG NINH PROVINCE - Tri Son, Ha; Hai Hoa, Nguyen; Van Truong, Vu (Journal of Forestry Science and Technology, 2023)
This study focused on mangrove cover mapping by using vegetation indices in Tien Yen district. Mangrove ecosystems play a vital role in many coastal regions, protecting against erosion and storm surges, providing nursery habitats of aquatic organisms, and offering livelihoods to local communities. Besides, this study aims to evaluate the use of PlanetScope data based on vegetation indices for mapping mangrove cover. This study collected and analyzed high-resolution PlanetScope satellite imagery (3m x 3m) to calculate eight different vegetation indices, including CMRI, NDVI, NDWI, GNDVI, BNDVI, SAVI, IPVI, and EVI2. These indices were used to map the mangrove cover in Tien Yen District and to evaluate the accuracy of each vegetation index. The results showed that among all of the indices used, NDVI had the highest accuracy of 96.3% in mapping the mangrove cover in Tien Yen district, followed by CMRI. Besides, the study emphasizes the importance of utilizing remote sensing techniques in supporting conservation efforts and establish sustainable management practices for mangrove forests in Tien Yen district. Additionally, the study presents an overview of the current situation and policy recommendations for the integrated management of mangrove forests, and provides information on sustainable mangrove ecosystem management in the context of climate change adaptation and mitigation in Tien Yen district, Quang Ninh province.